Níveis séricos maternos de estradiol, estriol e progesterona em partos induzidos com dinoprostona em gestantes a termo - Konopka, Cristine Kolling (2011)
Hormonal-mediated uterine quiescence involves the maintenance of a decreased inflammatory responsiveness. However, no study has investigated whether labor induction with prostanoids is associated with changes in maternal serum hormones. The objective of this study was to determine whether changes in circulating levels of progesterone, estradiol and estriol from admission to delivery are associated with successful labor induction with dinoprostone. A cohort of 81 pregnant women at term was followed from admission to birth until delivery, during the period of 2010-2011. The study was performed at the Hospital of the Federal University of Santa Maria, a tertiary care hospital. Unselected subjects were recruited and blood samples were obtained at admission and immediately before delivery. Sixteen patients had vaginal delivery after spontaneous labor, 12 required emergency cesarean after spontaneous labor and 16 underwent elective cesarean. Thirty-seven patients had labor induction with dinoprostone. Eligible patients received a vaginal insert of dinoprostone (10 mg), and patients were followed up until delivery. Progesterone (P4), estradiol (E2) and estriol (E3) plasma level and P4/E2, P4/E3 and E3/E2 ratio changes were observed from admission to immediately before birth, and the association of these measures with the resulting clinical classification outcome (route of delivery and induction responsiveness) were assessed. Progesterone plasma level decreased from admission to delivery in patients who underwent successful labor induction with dinoprostone [vaginal and cesarean delivery after induced labor: 23% (P<0.001) and 18% (P<0.025) decrease, respectively], but not in those whose induction failed (6.4% decrease, P>0.05). Estriol and estradiol levels did not differ between groups. Successful dinoprostone-induced labor was associated with maternal progesterone level decrease along time. While a causal relationship between progesterone decrease and effective dinoprostone-induced labor can not be established, it is tempting to propose that it may contribute for progesterone withdrawal and favor labor induction in humans.